2017
DOI: 10.1016/j.cub.2017.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule Tip Tracking by the Spindle and Kinetochore Protein Ska1 Requires Diverse Tubulin-Interacting Surfaces

Abstract: Summary The macromolecular kinetochore functions to generate interactions between chromosomal DNA and spindle microtubules [1]. To facilitate chromosome movement and segregation, kinetochores must maintain associations with both growing and shrinking microtubule ends. It is critical to define the proteins and their properties that allow kinetochores to associate with dynamic microtubules. The kinetochore-localized human Ska1 complex binds to microtubules and tracks with depolymerizing microtubule ends [2]. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…These so-called end-on attachments persist during polymerization and depolymerization of the dynamic ends of microtubules, and couple pulling forces produced by depolymerizing microtubules to chromosome movement (Akiyoshi et al, 2010;Grishchuk et al, 2005;Miller et al, 2016;Powers et al, 2009;Volkov et al, 2018). Furthermore, kinetochores control the dynamics of the plus ends, likely by balancing the action of MCAK (kinesin-13, a microtubule depolymerase) and Kif18 (kinesin 8, a microtubule stabilizer) and possibly other plus end-associated proteins Monda et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These so-called end-on attachments persist during polymerization and depolymerization of the dynamic ends of microtubules, and couple pulling forces produced by depolymerizing microtubules to chromosome movement (Akiyoshi et al, 2010;Grishchuk et al, 2005;Miller et al, 2016;Powers et al, 2009;Volkov et al, 2018). Furthermore, kinetochores control the dynamics of the plus ends, likely by balancing the action of MCAK (kinesin-13, a microtubule depolymerase) and Kif18 (kinesin 8, a microtubule stabilizer) and possibly other plus end-associated proteins Monda et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Such biochemical property of the Ska complex might allow it to harness the force generated by the peeling protofilaments to track on the depolymerizing microtubules. This microtubule end‐tracking capacity has recently been demonstrated to require diverse tubulin‐interacting surfaces of Ska1 . Interestingly, it has also been shown that the Ska complex confers this microtubule end‐tracking capacity to the Ndc80 complex in vitro .…”
Section: Ska Promotes End‐on Kinetochore Attachmentsmentioning
confidence: 97%
“…Several plus‐end tip‐tracking proteins that associate with elongating MTs through the end‐binding (EB) family of proteins can simply be considered as “hitchhiker” molecules and not “autonomous” tip trackers. However, in vitro analyses indicate that the Ska1 complex is capable of tracking polymerizing MTs independent of EB1 (Monda et al, ). Monda et al observed bright GFP‐Ska fluorescence at the growing MT ends (Figure a2).…”
Section: Introductionmentioning
confidence: 99%
“…Monda et al observed bright GFP‐Ska fluorescence at the growing MT ends (Figure a2). In addition, when MT depolymerization was induced by the removal of soluble tubulin, the Ska1 complex was also enriched at the shortening MT ends (Monda et al, ). Thus, the Ska complex exhibits the remarkable ability to remain associated with both the polymerizing and depolymerizing MT plus‐ends, a property that has thus far been reported only for one other human kinetochore MAP, the CENP‐E motor (Gudimchuk et al, ).…”
Section: Introductionmentioning
confidence: 99%